Aortic aneurysm management results through one year with a conformable neck sealing endograft and preemptive sac embolization with shape memory polymer devices - Dipankar Mukherjee, MD; Jihui Li, MD, PhD; David Spinosa, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Management of abdominal aortic aneurysm includes reducing the incidence of endoleaks and promoting sac regression. Sac embolization has been shown to promote regression but alone may not adequately address type II endoleak risk. We present three cases with challenging anatomy and follow-up data through 12 months after treatment. Patients were treated with endografts, and shape memory polymer embolization plugs were used to embolize the residual lumen volume outside of the endograft during the procedure. Follow-up imaging indicates that this procedure was used successfully in these patients. None of the patients developed sac expansion or developed type II endoleaks.